Visible-Light-Enabled Lanthanum-Mediated Intramolecular Epoxy-Ring Opening/Dehydrogenative Lactonization - Cai, Lina; Lai, Qihong; Zhang, Lele; Xue, Guotao; Zhang, Yirui; He, Na; Huang, Mingqiang; Hu, Shirong; Cai, Shunyou (Organic letters, 2023)
Catalytic C(sp3)–H functionalization has afforded great opportunities to prepare organic substances, facilitating the derivatization of complex drugs and natural molecules. This letter describes an efficient and practical protocol for lanthanum-catalyzed continuous epoxy-ring opening and oxidative dehydrogenative lactonization under visible-light irradiation. Notably, the lanthanum catalyst also acts as a photocatalyst while acting as a Lewis acid in this reaction; therefore, no additional photocatalyst is required. We can conveniently prepare a series of diverse isochromanones with oxygen-containing spirocyclic structural units under a balloon-oxygen atmosphere at room temperature. Mechanistic studies and control experiments reveal that the in situ-generated lanthanum bromide should be crucial in the reaction.